2006
DOI: 10.1016/j.ijid.2005.09.005
|View full text |Cite
|
Sign up to set email alerts
|

HIV, HBV, HCV, and syphilis co-infections among patients attending the STD clinics of district hospitals in Northern India

Abstract: A substantial percentage of the outpatients seen in the clinics of the district hospital in Uttar Pradesh harbor HIV and viral hepatitis infections, which otherwise would remain undiagnosed without serological screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 18 publications
3
29
3
Order By: Relevance
“…There is increasing evidence that triple infections of HIV/HBV/HCV is a common unrestricted health issues 2 which affects the clinical course of the disease [3][4] . They are overwhelming disease agents that shared modes of transmission [5][6][7] , thus HIV infected individuals are at risk of dual or triple infections with HBV and HCV infections 8 . Long-lasting infections with HIV, HBV, and HCV are major public health problems 6 which may potentially be as a result of virological interactions and could have an underlying immunological mechanism 4,[9][10] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is increasing evidence that triple infections of HIV/HBV/HCV is a common unrestricted health issues 2 which affects the clinical course of the disease [3][4] . They are overwhelming disease agents that shared modes of transmission [5][6][7] , thus HIV infected individuals are at risk of dual or triple infections with HBV and HCV infections 8 . Long-lasting infections with HIV, HBV, and HCV are major public health problems 6 which may potentially be as a result of virological interactions and could have an underlying immunological mechanism 4,[9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Dual infections with HIV/HBV or HIV/HCV and triple infections with HIV/HBV/HCV is also vastly prevailing among intravenous drug users (IDUs) [11][12][13] . Amongst the transmissible blood-borne viruses through the parenteral route (blood transfusion and sexual intercourse), HIV, HBV and HCV are significant and have numerous consequences 6,[13][14][15] . However, epidemiology of HIV-HBV-HCV triple infections varies as a result of differences in background of hepatitis infections and routes of HIV transmission 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted in a hospital-based population at Kathmandu Medical College Hospital, Nepal, the prevalence rate of Hepatitis B surface antigen was found to be 2.5% 8 which coincided with the present study (2.5%). In India a low prevalence of 1.0% has been reported by Hussain et al 9 Seroprevalence of HCV infection varied among hospital based populations in different regions of India. More Seroprevalence rates (4.8%) were reported from Pondicherry 10 followed by Jodhpur (2.46%).…”
Section: Discussionmentioning
confidence: 94%
“…Analysis of our results showed that age and sex influenced the prevalence rates of HIV, HBV and HCV infections like that of other studies ( Figure 1& 2). 9,13,14 The higher prevalence of these viral infections in the age group of 21-50 is attributable to the higher sexual activity of this age group. (Figure 2).…”
Section: Discussionmentioning
confidence: 99%